Exposed why our health insurance is incomplete and what can be done about it - Robertson, Christopher T., 1975- (Harvard University Press, 2019)
"In Exposed, Christopher Robertson looks at a widely-shared point of agreement in the political battle over how to reshape U.S. healthcare: Nearly all sides believe that health insurance coverage should be incomplete. Driven by a particular economic theory of valuation, the law now reflects this consensus that patients should bear a substantial part of the costs of their own healthcare. In theory, this strategy empowers patients to make cost-benefit tradeoffs as they decide which healthcare to consume, and it could thereby be a force for efficiency in a healthcare system that is rife with waste. But, in fact, this approach to financing healthcare can erode the very purposes of insurance, as it keeps people from valuable care and drives patients into bankruptcy. Contrary to the traditional economic theory of "moral hazard," Robertson identifies the real problems driving wasteful healthcare spending as a lack of good scientific evidence about what healthcare works. Exposed develops an alternative economic framework to understand the real purpose of insurance, pooling resources to provide access to care that would otherwise be unaffordable to individuals"--